Current Management of Pediatric Patients with Post-Burn Scars: Case Study - Larisa S. Kruglova; Anna G. Stenko; Lyubov A. Rubtsova; Mariya S. Kruglova (Вопросы современной педиатрии)
Background. Post-burn scars are common among pediatric patients. Pathological scarring is clear indication for conservative or surgical management of pediatric patients who continue to grow and develop after the resolution of burn injuries. Such lesions can significantly reduce patients' quality of life and, moreover, cause significant functional and aesthetic discomfort. Clinical cases description. The results of observation over two children (2 years 7 months and 12 years) with developing post-burn scars are demonstrated. Successful management method using physiotherapeutic complex (including monopolar radiofrequency treatment combined with ultrasound therapy, photodynamic therapy, and close-focus X-ray therapy) is presented. Conclusion. Modern trends in post-burn scars management are based on timely implementation of effective and safe methods early on rehabilitation stages and tissue restoration after burn injury to prevent pathological scarring and achieve control over its activity.